Hepatoprotective Activity of Pongamia pinnata Leaves on Antitubercular Drugs Induced Hepatotoxicity in Rats - Derangula, Samba Siva Raju; Muthiah, N. S.; Somashekar , H. S.; Sukumar , E. (Pharmaceutical Research - Recent Advances and Trends Vol. 1, 2024)
Aim: The present study highlights the hepatoprotective effect of ethanolic extract of the leaves of the plant Pongamia pinnata on antitubercular drugs (isoniazid and rifampin) induced hepatotoxicity in rats. Introduction: The hepatotoxic character of a drug is only discovered after it has gone on sale. The most common reason for taking drugs off the market is Drug Induced Liver Injury (DILI), which calls for labelling changes. Research evidence stated that anti-tubercular medication-induced liver damage is mainly due to oxidative stress which primes to cell injury and apoptosis in humans. Methods: The experiment used five groups of male Wistar rats, each with six animals. Two control groups were given gum acacia and a mixture of isoniazid and rifampin. The two other groups received 200 and 400 mg/kg body weights of ethanolic extract from the leaves of Pongamia pinnata respectively. The fifth group was given silymarin (50mg/kg, p.o.). The concentrations of serum Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Alkaline Phosphatase (ALP), tissue Malondialdehyde (MDA) and thiols were estimated in the blood of all animals. One-way ANOVA was used for statistical analysis followed by Tukey's test. Results: When rats were given the mixture of anti-tubercular drugs and high dosage (400 mg/kg) of ethanolic extract of Pongamia pinnata, the blood enzymes showed lower levels than antitubercular treated groups. The co-administration of a high dose of Pongamia pinnata extract with antitubercular drugs reduced MDA levels and elevated thiol levels considerably (p< 0.05). These biochemical marker levels however were not adjusted. Conversely, supplementation with Pongamia pinnata attenuated all the changes prompted by the antitubercular drugs and protected the hepatocytes from oxidative destruction revealing the hepatoprotective, antioxidant, antiapoptotic and membrane stabilising action of Pongamia pinnata leaves against drugs-induced toxicity. Conclusion: In rats, Pongamia pinnata encompasses a partial protective effect against the hepatotoxicity caused by anti-tubercular drugs at high doses.